Contribución de las energías renovables no convencionales al sistema de gestión integral de energía en Colombia (2018)
The energies coming from fossil fuels are not an infinite resource, by the way, they tend to be somewhat scarce. Normally, they are located in politically unstable geographical areas, and both their transport and their use cause a series of impacts on the environment and health, which are highly serious. Therefore, the human being will be in need of using the sun, wind, biomass and water to meet the energy needs, according to the resources of each country.